Does different vertical position of maxillary central incisors in women with different facial vertical height affect smile esthetics perception? - Ezgi Atik; Hilal Turkoglu (SpringerOpen, 2023)
Abstract Background The aim of this study was to assess the esthetic perceptions of orthodontists, prosthodontists and laypersons with regard to different vertical positions of the maxillary central incisors related to lateral incisors for different facial vertical height cases. Subject and methods Frontal full-face photographs showing social smiles of three adult women aged between 18 and 25 years were used. Vertical position of the maxillary central incisor was changed (intruded or extruded) with 0.5 mm increments according to the reference gingival line resulting five images for each woman in a full-face view yielding a total of 15 images. A visual analog scale was placed below each smile to allow the raters to evaluate the attractiveness of each smile independently. One-way analysis of variance was used to determine whether there was a difference between more than two independent groups in terms of quantitative variables. Comparisons of more than two dependent groups were examined with repeated measures one-way ANOVA. The significance level was taken as 0.05 for all analyses. Results For increased facial vertical height, the highest scores for orthodontists were given to the 0.5 mm extruded (64.18 ± 26.36), for prosthodontists to the control (57.28 ± 19.80), and for layperson to the 1 mm extruded (61.27 ± 25.98) central incisor position. For decreased facial vertical height, the highest scores were obtained at the 0.5 mm intrusion with an increasing pattern from orthodontists to laypersons (63.95 ± 22.08 for orthodontists, 79.87 ± 21.43 for prosthodontists, and 79.88 ± 19.17 for laypersons). All three rater groups gave the highest scores to the 0 mm (control) smile design for normal facial vertical height. When these scores were compared among the groups, laypersons gave significantly higher scores compared to orthodontists (p < 0.001) and prosthodontists (p = 0.005). Conclusions The facial vertical height significantly affected the perception of smile esthetics. Keeping the distance between the central and lateral incisors longer than 1 mm in individuals with increased facial height may be important in terms of increasing patient satisfaction in terms of clinical aesthetics. On the contrary, keeping the distance between the central and lateral incisors shorter than 1 mm may create a more esthetically acceptable result in individuals with short facial height.